STUDENTS’ PERCEPTION OF USING PADLET IN LEARNING ENGLISH - Setiawati Setiawati (STAI Hubbulwathan Duri, 2020)
This study aimed to know students’ perception of using Padlet in learning English in the first semester of Islamic Education Department STAI Hubbulwathan Duri. This research used a quantitative approach. The design of the research was a survey. In this research, the writer conducted a descriptive survey. The total population was the first semester of Islamic education STAI Hubbulwathan Duri. The undergraduate students have the same qualification and academic background before doing a survey. They had ever learned English by using Padlet. The sample of this research was 61 respondents. The total rating percentage of students’ perception using Padlet in learning English 54.5%. it was the agreed category. This category showed the respondents Agree to use Padlet application in the teaching-learning process. Based on the overall mean is 3.15 and the standard deviation is 0.673 respondents agree used it in the teaching-learning process. The respondents gave positive responses. It meant that the Padlet platform gave a positive perception to use it in the English learning process.